The Application of Sak-Emkm as a Basis For Preparing Msme Financial Statements (Case Study In UD. Kotamobagu Fragrance Light) - Makalalag, Magdalena; Hullah, Abdurahman (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Public awareness for entrepreneurship, especially MSME actors by taking advantage of existing opportunities, is not followed by understanding and knowledge about the importance of managing a business well. The business community is still unaware of the importance of good financial records and based on applicable standards. The recording of financial transactions is still carried out simply, and some transactions that should have been recorded were not recorded. Because not carrying out proper accounting records causes MSME actors to lack understanding of the preparation of financial statements. This research aims to apply SAK-EMKM as a Basis for Preparing MSME Financial Statements (Case Study at UD. Kotamobagu Aroma Light). This research uses qualitative research methods with a descriptive approach. Data analysis techniques begin by using content analysis, namely making transcripts of interviews, listening carefully, then writing down the words heard according to what is in the recording. The results showed that UD. Cahaya Aroma Kotamobagu has not prepared regular financial statements. This routine meaning is only when they will offer credit loans at the Bank to get KUR (Kredit Usaha Rakyat). In its creation, the company only fills in the format given incorrectly or only fabricates and does not comply with the actual financial statements. MSMEs do not use consultants or parties who know or understand the manufacturing process better. UD. Cahaya Aroma Kotamobagu also found several obstacles experienced by the preparation of financial statements, namely 1). There is a lack of awareness from MSME business actors in their financial management. 2) lack of human resources who have the ability to prepare financial statements and it is too expensive if business owners use employees to help existing businesses. 3). Management is done by the owner himself, so the owner only thinks about sales every day to be able to make a profit.